Riemann-Liouville and Caputo Fractional Approximation of Csiszar’s f-Divergence - Anastassiou, George A. (Sarajevo Journal of Mathematics, 2024)
Here are established various tight probabilistic inequalities that give nearly best estimates for the Csiszar's f-divergence. These involve Riemann-Liouville and Caputo fractional derivatives of the directing function f. Also a lower bound is given for the Csiszar's distance. The Csiszar's discrimination is the most essential and general measure for the comparison between two probability measures. This is continuation of [4]. 2000 Mathematics Subject Classification. 26A33, 26D15, 28A25, 60E15